Human Papilomavirus of women with oncotic cytologic normal - Noronha, Vânia Lúcia; Noronha, Rafael; Carmona, Bruno; Macedo, Luis Antônio; Cruz, Ermelinda M.; Naum, Cecília; Mello, Wyller; Villa, Luisa (Brazilian Journal of Sexually Transmitted Diseases, 2005)
Introduction: among vírus of sexual transmission, HPV is the most prevalent. It can be detected in a great number of sexual active women in a clinical latent stage. Objetives: to verify “latent” infection of HPV in uterine cervix in women that had oncotic citology in range of “normalit”. Methods: among 433 women, age 30 to 45 years old, submitted to screening of uterine cervical cancer with normal citologic result, it in endocervical samples. The rest of clinical specimen was dived in solution of PBS from cervicalextraction of DNA and molecular tests respectively Instituto Ludwig de Pesquisas Sobre o Câncer. Results: prevalence of HPV was 6,9%; 91,5% of them had being submitted at least to one colpocitologicalexam; there was a positive correlation between the prevalence of the virus and the number of sexual partnees, but without significant association. Agreat number of women (315/433, 73%) started their sexual activities before 20 years old. More prevalence of HPV was observed in the group whichfirst sexual intercourse occurred up to 14 years old. Other possible cofactors associated witch the riskof HPV and uterine cancer were evoluated, with no significant correlation. Conclusion: the prevalence of the HPV in the sample was not so hight as expected, probably because the sample didnot enrore women at age of greatest risk . It was observed that precious sexual activies played a great role.